2003
DOI: 10.1161/01.str.0000064326.65899.ac
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function Under Aspirin, Clopidogrel, and Both After Ischemic Stroke

Abstract: Background and Purpose-Combined antiplatelet agents may offer additive protection over single drugs after stroke. We investigated whether platelet activation is reduced under combined aspirin and clopidogrel compared with each drug alone. Methods-In a case-crossover study, 31 patients with previous atherothrombotic or lacunar stroke who were treated with aspirin (100 to 300 mg/d) received clopidogrel (75 mg/d) and both aspirin and clopidogrel for 4 weeks. Platelet function in whole blood was studied after each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 34 publications
3
51
2
Order By: Relevance
“…1) [10,12,13,14,15,22,23,24]. A total of 18 studies were excluded: four were excluded because they were not RCTs [25,26,27,28], three were excluded because the comparator was not aspirin or clopidogrel alone [29,30,31], seven were excluded for lack of specific data [9,32,33,34,35,36,37], two were excluded since the trials were ongoing [38,39], and two were excluded due to redundancy [40,41]: the original study reported both primary and secondary prevention, and the subsequent report [14] focused on results in patients with previous TIA or ischemic stroke. The baseline characteristics of included studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) [10,12,13,14,15,22,23,24]. A total of 18 studies were excluded: four were excluded because they were not RCTs [25,26,27,28], three were excluded because the comparator was not aspirin or clopidogrel alone [29,30,31], seven were excluded for lack of specific data [9,32,33,34,35,36,37], two were excluded since the trials were ongoing [38,39], and two were excluded due to redundancy [40,41]: the original study reported both primary and secondary prevention, and the subsequent report [14] focused on results in patients with previous TIA or ischemic stroke. The baseline characteristics of included studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Along with standard platelet aggregation, PFA-100 has been used to monitor antiplatelet therapy in patients with ischemic stroke 17,[23][24][25][26] The method uses a combination of 2 agonists, collagen/epinephrine or collagen/ADP, to stimulate platelet aggregation. Measuring PFA-100 closure time has potential for monitoring the inhibitory effects of various antiplatelet drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, except for the study of Grundmann et al, 17 most previous studies were not able to show that PFA-100 can predict the recurrence of ischemic stroke, suggesting that the platelet aggregation approach may have limitations in monitoring antiplatelet therapy with various antiplatelet drugs. In other attempts to evaluate platelet activation, expression levels of platelet receptors, including P-selectin (CD62p), 23 lysosome-associated membrane protein (CD63), 23 PECAM-1 (CD31), 26 GP IIb/IIIa (CD41), 26 Figure 2. Recurrence rates of quartiles according to platelet aggregation in the aspirin group.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast, another study found that, the PFA-100 system was sensitive to clopidogrel effects in a subset of stroke patients. 11 Another recent study reported a considerable time lag before relevant clopidogrelinduced antiplatelet effects could be measured in stroke patients. 12 With respect to a possible delay in the detection of antiaggregatory effects, we further analyzed our data and stratified the study population into 2 groups; stroke patients treated with clopidogrel for Ͻ3 weeks and Ͼ3 weeks (short-term vs long-term therapy).…”
Section: Discussionmentioning
confidence: 99%